PENGUKURAN SPEKULASI DI PASAR MODAL SYARIAH - Sumar’in Sumar’in (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Speculation is a profit-making technique by only playing with risks. Speculators only use intuition and do not really use information in making decisions about buying or selling shares. This article explains and details how Islam views and reduces speculation in the Islamic capital market. The large amount of speculation is a result of margin trading expectations for the shares they own. In an effort to minimize these actions, of course a Minimum Holding Period (MHP) mechanism must be created, meaning that shares cannot easily be bought and sold on the spot. The rolling system of settlement is only justified when the shares being traded are actually owned by the seller.